PKC-ζ Aggravates Doxorubicin-Induced Cardiotoxicity by Inhibiting Wnt/β-Catenin Signaling - Yan-Jun Cao; Jing-Yan Li; Jing-Yan Li; Pan-Xia Wang; Zhi-Rong Lin; Wen-Jing Yu; Ji-Guo Zhang; Jing Lu; Pei-Qing Liu; Pei-Qing Liu (Frontiers Media S.A., 2022)
Doxorubicin (Dox) is a chemotherapeutic drug used to treat a wide range of cancers, but its clinical application is limited due to its cardiotoxicity. Protein kinase C-ζ (PKC-ζ) is a serine/threonine kinase belonging to atypical protein kinase C (PKC) subfamily, and is activated by its phosphorylation. We and others have reported that PKC-ζ induced cardiac hypertrophy by activating the inflammatory signaling pathway. This study focused on whether PKC-ζ played an important role in Dox-induced cardiotoxicity. We found that PKC-ζ phosphorylation was increased by Dox treatment in vivo and in vitro. PKC-ζ overexpression exacerbated Dox-induced cardiotoxicity. Conversely, knockdown of PKC-ζ by siRNA relieved Dox-induced cardiotoxicity. Similar results were observed when PKC-ζ enzyme activity was inhibited by its pseudosubstrate inhibitor, Myristoylated. PKC-ζ interacted with β-catenin and inhibited Wnt/β-catenin signaling pathway. Activation of Wnt/β-catenin signaling by LiCl protected against Dox-induced cardiotoxicity. The Wnt/β-catenin inhibitor XAV-939 aggravated Dox-caused decline of β-catenin and cardiomyocyte apoptosis and mitochondrial damage. Moreover, activation of Wnt/β-catenin suppressed aggravation of Dox-induced cardiotoxicity due to PKC-ζ overexpression. Taken together, our study revealed that inhibition of PKC-ζ activity was a potential cardioprotective approach to preventing Dox-induced cardiac injury.